Estimating the Cost of student Training Using Activity-Based Costing (ABC) Method in the Department of Health Management and Economics at the School of Public Health, Tehran University of Medical Sciences - Rajabali Daroudi; Mahmoud Zamandi (Tehran University of Medical Sciences, 2023)
Background and Aim: The role of accurate information in decision-making and programs implementation has highlighted the need to design an appropriate costing system. The present study aimed to estimate the cost of student Training in the Department of Health Management and Economics at the School of Public Health, Tehran University of Medical Sciences using activity-based costing. Materials and Methods: This research was an applied, descriptive, and cross-sectional study. In this study, all information was collected through interviews with seven officials, financial and administrative staff, and also by using available documents in the faculty. To analyze the costs, the administrative and educational sections were classified into three levels including overhead, middle, and final activity centers, and, using appropriate bases and Microsoft Excel 2013 software, costs of overhead, middle, and final activity centers, and finally, the total cost of each student was calculated. Results: In this study, the total cost of education for each Ph.D. and master's student in the department of health management and economics was estimated as 1.95 billion and 376 million IR Rials, respectively. So that the cost of each year of Ph.D. and master's student education was 433 and 150 million IR Rials, respectively. Out of the total costs of the Department of Health Management and Economics, only 22% of the costs were related to overhead and middle activity centers, and 78% of the costs were exclusive to the final activity center, and the majority of these costs (97%) were related to the personnel, especially the faculty members.  Conclusion: The cost of training Ph.D. students due to the high coefficient of the degree and thus increasing the importance (cost share) of the field, receiving a scholarship from the Ministry of Health and a longer period of study, was estimated to be about 5 times that of a master's degree. The Ministry of Health and universities can design and implement targeted research programs with the help of faculty members and graduate students, especially Ph.D. students, to solve problems and improve the health of the community, thus improving resource efficiency and productivity.